Biological Mediators and Partial Regulatory Mechanisms on Neuropathic Pain Associated With Chemotherapeutic Agents - Liu, Z; Liu, S; Zhao, Y; Wang, Q (Physiological research, 2024)
One of the most common issues caused by antineoplastic agents is chemotherapy-induced peripheral neuropathy (CIPN). In patients, CIPN is a sensory neuropathy accompanied by various motor and autonomic changes. With a high prevalence of cancer patients, CIPN is becoming a major problem for both cancer patients and for their health care providers. Nonetheless, there are lacking effective interventions preventing CIPN and treating the CIPN symptoms. A number of studies have demonstrated the cellular and molecular signaling pathways leading to CIPN using experimental models and the beneficial effects of some interventions on the CIPN symptoms related to those potential mechanisms. This review will summarize results obtained from recent human and animal studies, which include the abnormalities in mechanical and temperature sensory responses following chemotherapy such as representative bortezomib, oxaliplatin and paclitaxel. The underlying mechanisms of CIPN at cellular and molecular levels will be also discussed for additional in-depth studies needed to be better explored. Overall, this paper reviews the basic picture of CIPN and the signaling mechanisms of the most common antineoplastic agents in the peripheral and central nerve systems. A better understanding of the risk factors and fundamental mechanisms of CIPN is needed to develop effective preventive and therapeutic strategies.
Keywords: nádory; protinádorové látky; neuralgie; signální transdukce; Signal Transduction; Antineoplastic Agents; Animals; Neuralgia; Humans; lidé; zvířata; Neoplasms